1973
DOI: 10.1128/am.26.3.264-267.1973
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Herpes Simplex Virus Infection by Phosphonoacetic Acid

Abstract: Disodium phosphonoacetate when administered orally or topically to mice experimentally infected with herpes simplex virus was able to significantly reduce the mortality associated with the agent. In addition, this compound was able to reduce herpesvirus lesions on the corneas of infected rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

1976
1976
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Since the original report of the suppression of herpes simplex virus (HSV) in rabbits by phosphonoacetic acid (l),1 Gerstein et al 2 have reported 1 to be equivalent to idoxuridine against an established herpes infection in rabbits. Phosphonoacetic acid has been shown to specifically inhibit HSV-induced DNA polymerase.3 These promising early results with 1 encouraged a synthetic program to find an analogue of 1 with an improved therapeutic ratio. Prior to the start of the synthetic program, J. Mao (unpublished results) had found simple P-diesters of 1 [(R0)2P(0)CH2C02H] to be inactive against HSV-induced DNA polymerase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the original report of the suppression of herpes simplex virus (HSV) in rabbits by phosphonoacetic acid (l),1 Gerstein et al 2 have reported 1 to be equivalent to idoxuridine against an established herpes infection in rabbits. Phosphonoacetic acid has been shown to specifically inhibit HSV-induced DNA polymerase.3 These promising early results with 1 encouraged a synthetic program to find an analogue of 1 with an improved therapeutic ratio. Prior to the start of the synthetic program, J. Mao (unpublished results) had found simple P-diesters of 1 [(R0)2P(0)CH2C02H] to be inactive against HSV-induced DNA polymerase.…”
mentioning
confidence: 99%
“…Simple alkylcarboxyl esters of 1 may be prepared by direct esterification of 1 with the appropriate alcohol and HC1.4 Compounds 2 and 3 were prepared by this method. A more versatile method of preparation of carboxyl esters of 1 was suggested by a paper by Hata and Sekine.5 These workers reported the reaction of tris-(trimethylsilyl) phosphite [(Me3SiO)3P] and 5'-bis(trimethylsilyl) phosphite esters of nucleosides with diphenyl disulfide to give S-phenylphosphorothioates. A successful Arbuzov reaction with (Me3SiO)3P and the appropriate chloroacetate would provide ready access to carboxyl esters of 1. When a solution of (Me3SiO)3P and benzyl chloroacetate was heated to 165 °C, a vigorous reaction occurred as evidenced by the formation of chlorotrimethylsilane.…”
mentioning
confidence: 99%
“…Although the medication was discontinued after 4 days, no relapse of infection was observed in the group of animals by day 7 when only a few scabs remained. Scab formation in the placebo-treated animals was observed only after 7 days.…”
mentioning
confidence: 94%
“…1975, 234, 195. (5) Spitzer, R. L., chairperson "Diagnostic and Statistical Manual of Mental Disorders"; American Psychiatric Association: a Results in this table were calculated by subtracting the percent correct scores of control group from those of the drug group. 6 Drugs administered ip 1 h prior to retention testing. c Not testable, mice too excited.…”
mentioning
confidence: 99%
“…(5) The cyclic lactam must be the pyrrolidin-2-one, as the corresponding piperidin-2-one with a usually effective side chain (41) is markedly less active. (6) The acetamide spacing is critical, since the corresponding propionamide (42), with a good side chain, is almost inactive. (7) The presence of the inverted U-shaped doseeffect curve can be seen repeatedly in the results in Table II.…”
mentioning
confidence: 99%